PENGARUH PEMBERIAN HIDROTERAPI (RENDAM KAKI AIR HANGAT) TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SIKUMANA KOTA KUPANG - Yustus Anselmus Arianto Malaibel (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
ABSTRACT Hypertension is called the silent killer because it is a disease that does not show typical symptoms. Non-pharmacological therapi is an independent action one of them is hydrotherapy (warm water foot soaking), which is very simple and natural. The purpose of this study was determine the effect after warm water foot soaking therapy indescrease blood pressure in patients with hypertension in the working area of Sikumana Public health centerkupang city. The study used design of the pre-postest with control groupdesign with total sampling. There ware 60 respondents selected though, devided into 30 respondents for intervention group and 30 respondents for control group. The results of the study indicated that the characteristics of respondents based on age in the intervention group 50.0% and the control group 43.3% at the age of 50-59 years, based on sex in the intervention group female sex 56.7% and groups male sex control 60.0%. Based on the wilcoxon test there was differences in blood pressure before and after hydrotherapy (warm water foot soaking) in the intervention group and the control group, whitsystolic and diastolic p-value in the intervention group p-value = 0.00 and p-value = 0.00 and in the control group p-value = 0.46 and p-value = 0.01. Based on the mann-whitney test the comparison of blood pressure before and after hydrotherapy warm water foot soaking in the intervention group and the control group p-value = 0.00. These results indicate that there is an influence hydrotherapy (warm water foot soaking)in decreasing blood pressure in hypertensive patients in the working area of ​​puskesmassikumanakupang city. Suggestion: For the Public health center(warm water foot soaking) is expected that it can be used as an alternative therapy that can be recommended for patients with hypertension. Keywords: hypertension, hydrotherapy, soak feet of warm water, blood pressure.